Muscle hypertrophy and strength improvements following blood flow restriction combined with resistance training in team-athletes: a systematic review and meta-analysis - Huang, Q.; Xiao, L.; Zheng, S.; Meng, L.; Yue, S. (Frontiers in Physiology, 2026)
Objective: The purpose is to evaluate how blood flow restriction (BFR) and resistance training (RT), influence muscle adaptation and sports performance in team-athletes.